Estimation for filtering attacks on QIM watermarks - WANG Jin-shen; DAI Yue-wei; WANG Zhi-quan (Tongxin xuebao)
A scheme for estimating two-band amplitude scale attack within a quantization-based watermarking context was presented.Quantization-based watermarking schemes are not robust against linear time invariant（LTI） filtering attacks,on which a multi-band amplitude scaling attack that modifies the spectrum of the signal using an analysis/synthesis filter bank was concentrated.First the probability density function（PDF） of the attacked signal was derived.Second,using a simplified approximation of the PDF model,a maximum likelihood（ML） procedure for estimating two-band amplitude scaling factor was proposed.Finally,experiments were performed with synthetic audio signals showing the good performance of the proposed estimation technique under realistic conditions.